Factors Related to Visitors’ Experience of Orientation and Disorientation at MTC Karebosi Makassar - Musdaria Muhammadiah; Ria Wikantari; Afifah Harisah (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2020)
Architecture involves the perception of the personal environment and the community in designing to be able to orient users. That perception became the basis for designers to design public buildings. The shopping center is one of the most visited public buildings and often orients and disorients its users. MTC Karebosi is one of the shopping centers in Makassar with the concept of providing primary, secondary, and electronic merchandise needs in one place. The need can be purchased wholesale and retail at affordable prices which makes it one of the alternatives for people to shop in Makassar. As a place to sell wholesale and retail merchandise, the retails laying arrangements are designed to the maximum possible to get a large number of retails in a limited area. As a result, the existing retail looks solid and similar to each other. Because of that, the situation between the corridors to the destination looks similar to each other. These conditions make visitors unable to mark the corridors that pass to the destination so that sometimes visitors experience disorientation. This research aims to determine factors related to the visitor's orientation and disorientation experience and uses survey methods. Data collection uses questionnaires as research instruments. The results revealed that factors related to orientation are spatial aspects, functional aspects, visual aspects, cognitive mapping, and behavior. Factors related to disorientation are spatial aspects, functional aspects, visual aspects, cognitive mapping, behavior, and internal individuals. However, there is one different factor that is the individual internal factor in the disorientation experience whereas orientation is not found. This is because internal factors such as fatigue make it easy for a person to forget and not concentrate so that they experience disorientation.